2015
DOI: 10.1186/s12889-015-1687-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, medication, control, and risk factors associated with hypertension in Yi ethnic group aged 50 years and over in rural China: the Yunnan minority eye study

Abstract: BackgroundHypertension is an important public health issue in China, but there are few studies examining hypertension in ethnic groups in Yunnan, China. This study, Yunnan Minority Eye Study (YMES), was initially designed to determine the prevalence and impact of eye diseases, including hypertension and diabetes mellitus. As a part of YMES, the prevalence, awareness, treatment, and control of hypertension and the associated risk factors among the Yi ethnic population in rural China are reported.MethodsA popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“… 113 , 121 , 131 , 135 , 136 , 140 Importantly, hypertension rates were consistently higher among overweight/obese participants, compared to normal weight persons across all regions (mean prevalence 46.4% [95% CI 33.1–60.7] vs 26.3% [95% CI 15.8–37.8], P < 0.00001). 30 , 33 , 41 , 44 , 47 , 55 , 56 , 61 , 62 , 65 , 66 , 69 , 78 , 85 , 90 , 97 , 99 , 106 , 113 , 117 , 128 , 131 , 134 136 , 140…”
Section: Resultsmentioning
confidence: 99%
“… 113 , 121 , 131 , 135 , 136 , 140 Importantly, hypertension rates were consistently higher among overweight/obese participants, compared to normal weight persons across all regions (mean prevalence 46.4% [95% CI 33.1–60.7] vs 26.3% [95% CI 15.8–37.8], P < 0.00001). 30 , 33 , 41 , 44 , 47 , 55 , 56 , 61 , 62 , 65 , 66 , 69 , 78 , 85 , 90 , 97 , 99 , 106 , 113 , 117 , 128 , 131 , 134 136 , 140…”
Section: Resultsmentioning
confidence: 99%
“…There is a great gap in hypertension management between urban and rural residence in China, 18,19 and the rate of monitoring and follow-up among rural hypertensive adults was lower than that of urban hypertensive adults, which was consistent with earlier findings. 37 which may modify the estimated effects on incidence of depressive symptoms in our study. 37 which may modify the estimated effects on incidence of depressive symptoms in our study.…”
Section: Antihypertensive Treatment and Incident Depressive Symptomsmentioning
confidence: 99%
“…[34][35][36] Additionally, most of the health promotion activities, such as advocating rational use of drugs, and improving health behaviors like weight control, physical exercise, and healthy diet are commonly held in city communities, which caused a barrier to equal access for rural population. 37 Moreover, recent studies have indicated that although hypertension is typically asymptomatic and many patients look otherwise healthy, its inapposite detection and management may cause psychological stress since being diagnosed with hypertension were challenging to individuals' personality and caused a loss of self-esteem and therefore rendering patients psychologically stressful. 30,38 Fourth, except for hypertension management, prevention and treatment of depressive symptoms in urban areas is better than those in rural areas.…”
Section: Antihypertensive Treatment and Incident Depressive Symptomsmentioning
confidence: 99%
“…In previous reports, we have described the prevalence of hypertension in adult rural Chinese populations of the Bai nationality in Dali [12] and the Yi nationality in Shilin [13]. To facilitate the comparison among different nationalities, our data collection process in the Dai ethnicity is the same as that of the Bai and Yi nationalities.…”
Section: Study Population and Designmentioning
confidence: 99%